2020
DOI: 10.14202/vetworld.2020.2759-2764
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, molecular identification, and pathological lesions of Saprolegnia spp. isolated from common carp, Cyprinus carpio in floating cages in Mosul, Iraq

Abstract: Background and Aim: Saprolegniasis is a fungal disease that infects freshwater fish. The condition is characterized by a cotton-like appearance in the gills and body. This study aimed to isolate Saprolegnia from common carp, Cyprinus carpio, raised in a floating cage in Wana district, Mosul, Iraq. Materials and Methods: Samples were collected from 15 infected fish and examined microbiologically, molecularly, and histopathologically. Saprolegnia DNA was extracted which was amplified using universal primers giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…figure (1) numbers and percentage of Saprolegnia parasitica isolated from Diwaniyah river Ten isolates of the fungus Saprolegnia parasitica were subject to PCR and the PCR products were electrophoresed for the purpose of molecular diagnosis, and the diagnosis of all isolates was identical to the traditional diagnosis, which relies on the appearance of the fungus in plates and under an optical microscope, where the bands were at 568 bp. The use of the ITS region is one of the matters widely accepted in the field of diagnosis, as it is considered highly stable and gives accurate results, especially when using high-quality primers from original source [16,18,19]. The spacer DNA known as internal transcribed spacer (ITS) is located between the large-subunit and small-subunit ribosomal RNA (rRNA) genes on a chromosome, or it may be the homologous transcribed region in the polycistronic rRNA precursor transcript.…”
Section: Resultsmentioning
confidence: 99%
“…figure (1) numbers and percentage of Saprolegnia parasitica isolated from Diwaniyah river Ten isolates of the fungus Saprolegnia parasitica were subject to PCR and the PCR products were electrophoresed for the purpose of molecular diagnosis, and the diagnosis of all isolates was identical to the traditional diagnosis, which relies on the appearance of the fungus in plates and under an optical microscope, where the bands were at 568 bp. The use of the ITS region is one of the matters widely accepted in the field of diagnosis, as it is considered highly stable and gives accurate results, especially when using high-quality primers from original source [16,18,19]. The spacer DNA known as internal transcribed spacer (ITS) is located between the large-subunit and small-subunit ribosomal RNA (rRNA) genes on a chromosome, or it may be the homologous transcribed region in the polycistronic rRNA precursor transcript.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed that the gill tissue structure of grass carp infected with Saprolegnia was severely damaged in the untreated group with AEW, and gill laments were signi cantly necrotic and detached. Ali et al (Ali et al 2020) found that the muscle tissue of the infected carp was incomplete, with necrosis of muscle bres, oedema and moderate in ltration of in ammatory cells. In the present study, the histopathological symptoms of the muscles of grass carp infected with Saprolegnia were consistent with those observed by Ali et al In the treated group, the histopathological symptoms of the muscles of grass carp were less severe and the muscle bres were more intact.…”
Section: Discussionmentioning
confidence: 99%
“…A fungal DNA purification kit (Omega Bio‐Tek) was used to isolate DNA and quantified via a Nanodrop One c (ThermoFisher Scientific). The resultant DNA was used in PCR using the primer pairs ITS 1/ITS 4 primers (Ali et al., 2020) and ITS 4 alt/ITS 5 alt primers (Sarowar et al., 2019; Table 1). Products were checked on a gel, purified and sent to Eurofins Genomics (Huntsville, AL) for sequencing.…”
Section: Methodsmentioning
confidence: 99%